Composition Analysis Tools Pengerih Catches On Time Day And Night In Village Pergam Rupat Bengkalis District Riau Province - Mamri, Maizal; Rengi, Pareng; ', Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted on Juli 2014 in Pergam village waters, Rupat, Bengkalis District, Riau Province. This study aims to determine differences and composition of catches pengerih during the day and night, the best time for the operation pengerih, and other types of catch pengerih in Pergam Village, District Rupat, Bengkalis. The method used in this study is a survey method. From the results of research by type (tail) contained the highest number of catches at night time is 57612 tail and so are by weight (kg) at the most the night with weight 108.3 kg.based on the type of species caught are shrimp (Panaeus sp), fish (Fish), jellyfish (Aurelia sp), and squid (Loligo sp).Keyword : Stow net, Catches, Day and Night